Compressive mechanical properties of W-particle/Zr-based amorphous alloy composites. (24th May 2019) - Han, J L; Chen, X; Du, Z H; Fu, H M; Cheng, C; Xu, L Z; Wang, J B; Du, C X
Abstract: In order to study the effect of W-particle on compressive mechanical properties of Zr-based amorphous alloy, Zr-based amorphous alloy composites with the particle size of 100 μ m and W-particle volume fraction of 45% were prepared by stainless steel water quenching method. The quasi-static strain was collected by high-sensitivity strain gauge. The extension characteristics of the shear band were analyzed by scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS). Results show that: in the quasi-static experiment, W-particle changes the fracture morphology; Compared with Zr-based amorphous alloys, the compressive strength and strain of W-particle/Zr-based amorphous alloy composites increase by more than 21% and 96% respectively, and the elastic modulus of Zr-based amorphous alloy also increases accordingly; in the dynamic experiment, the W-particle hinders the extension of the shear band and the crack propagation, and increases the density of the primary and secondary shear bands in the Zr-based amorphous alloy, thus improving the compressive strength and strain of the Zr-based amorphous alloy. The primary and secondary shear bands and cracks appear in the dynamic compression fracture of Zr-based amorphous alloy so that the dynamic compressive strength is lower than the quasi-static one. From this point, W-particle changes this condition.